Prevalence of Intestinal Parasites and Clinical Manifestations in Children - M Ebadi; F Behravan; SH Hekmati Moghaddam (Tehran University of Medical Sciences, 2007)
Background: Diagnosis and treatment of parasitic infections are very important because of pathologic changes and clinical symptoms produced in the host, and for taking measures against them. These diseases have more adverse effects and more importance in children. This study was aimed at determining the prevalence of intestinal parasites and their clinical manifestations in children 0-14 years old referred to Yazd Central Laboratory. Methods: The present cross- sectional descriptive study was performed during the April 2005 to September 2006, with data obtained from the stool samples of 1500 children, using both wet mount smear (physiologic saline and Lugol΄s solutions) and formalin-ethyl acetate concentration method for detection of the intestinal parasites and also with the tape test for eggs of Enterobius vermicularis and Taenia. Results: From 1500 examined stool samples, 128(8.5%) cases were positive for one of the intestinal parasites, including 67(52.3%) females and 61(47.7%) males. Ninety five percent of positive cases were infected with protozoa and 5% with helminths. The most frequent protozoans were Blastocystis hominis 41.3%, Giardia lamblia 33.6%, and Entamoeba coli 14.7%. Enterobius vermicularis (4.3%) and Hymenolepis nana (0.7%) were the helminth species. The most abundant infection rate was shown in the 5-9 years old group, with a significant difference compared with other age groups (P< 0.05). About 87% of children infested with Blastocystis hominis showed more than 5 Blastocystis per 400x microscope fields, and 100% of children infested with Giardia lamblia and Chilomastix mesnili had clinical symptoms. Conclusion: In this study, lower contamination rates in comparison with the similar studies conducted in other regions of the country was seen, which may be as a result of the hot and dry climate and improved personal hygiene and public health services. There is a need for further studies about the prevalence and clinical symptoms of some parasites such as Blastocystis hominis and Chilomastix mesnili.